Der Magus unter Hexen: self-fashioning unter Hexereiverdacht: das Beispiel Thurneysser - Bulang, Tobias (Daphnis, 2025)
Abstract This article examines the interactions between Renaissance magicians and demonologists. Spaces for the legitimate practice of natural or white magic were opened around 1500 by Renaissance intellectuals who were challenging the general prohibition of any kind of magic by Augustine and Thomas Aquinas. Under the pressure of the growing persecution of witches, these spaces came under suspicion, including from demonologists who were publishing their arguments against magic of any kind. The study examines how magi reacted to this pressure, how they tried to present themselves in the face of the suspicion of witchcraft. The magus Leonhard Thurneysser zum Thurn, for example, publishes a variety of peculiar works to defend himself against accusations of black magic and necromancy.
Gesehen am 01.09.2025
Keywords: Dämonologie; Hexerei; Magier; Thurneysser zum Thurn, Leonhardt